2023
DOI: 10.1126/sciadv.ade9044
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire photochemical diodes for artificial photosynthesis

Abstract: Artificial photosynthesis can provide a solution to our current energy needs by converting small molecules such as water or carbon dioxide into useful fuels. This can be accomplished using photochemical diodes, which interface two complementary light absorbers with suitable electrocatalysts. Nanowire semiconductors provide unique advantages in terms of light absorption and catalytic activity, yet great control is required to integrate them for overall fuel production. In this review, we journey across the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 209 publications
0
10
0
Order By: Relevance
“…III–V semiconducting nanowire (NW) structures offer a great potential for high-performance (opto-)­electronic devices such as LEDs, lasers, , and heterobipolar transistors and for solar energy conversion devices such as solar cells or solar fuel devices. They can be engineered in a wide range of applications due to their tunable electronic band structure via the choice of material composition and doping profiles, e.g., for the integration of charge selective contacts, heterocontacts for tunnel junctions, or tunnel barriers. , Due to the high surface-to-volume ratio, special attention must be given to their surface and interfacial junctions, e.g., in the case of coaxial heterostructures …”
Section: Introductionmentioning
confidence: 99%
“…III–V semiconducting nanowire (NW) structures offer a great potential for high-performance (opto-)­electronic devices such as LEDs, lasers, , and heterobipolar transistors and for solar energy conversion devices such as solar cells or solar fuel devices. They can be engineered in a wide range of applications due to their tunable electronic band structure via the choice of material composition and doping profiles, e.g., for the integration of charge selective contacts, heterocontacts for tunnel junctions, or tunnel barriers. , Due to the high surface-to-volume ratio, special attention must be given to their surface and interfacial junctions, e.g., in the case of coaxial heterostructures …”
Section: Introductionmentioning
confidence: 99%
“…33−35 The strategy boosts V ph by increasing the band bending at the buried n + p junction relative to the p-SiNW|electrolyte interface. 35 Note that p-SiNW and n + p-SiNW exhibit almost identical lengths and diameters (Figure S3). We found that the doping shifted the E onset of M ox reduction more positively by 143 mV (Figure 1c), which we ascribe to the increased V ph (435 mV) of n + p-SiNW (Figure 1d).…”
mentioning
confidence: 95%
“…Shifting E onset more anodically can achieve energy-efficient photocathodic production of NADH. Thus, we constructed a radial n + p junction on the p-SiNW arrays by introducing arsenic atoms on the surface of the p-SiNW according to the literature. ,, The buried n + p interface induces a built-in electric field that enhances the separation of photoinduced charge carriers inside the photocathode. The strategy boosts V ph by increasing the band bending at the buried n + p junction relative to the p-SiNW|electrolyte interface . Note that p-SiNW and n + p-SiNW exhibit almost identical lengths and diameters (Figure S3).…”
mentioning
confidence: 99%
“…Finding sustainable and renewable energy is currently one of the most urgent challenges facing society today. With the sun providing 173 PW to the earth’s surface every year, or enough energy in 1 h to match the world’s yearly energy consumption, artificial photosynthesis offers an attractive route to using solar energy to produce fuels such as hydrogen, a fundamental component for building a carbon-free economy. ,, One such approach to realizing artificial photosynthesis is presented through the photochemical diode. , Photoanodes and photocathodes can be integrated through an ohmic contact, coupling both oxidative and reductive half-reactions in a single device. Conventional approaches targeted the optimization of the overall water splitting (OWS) reaction in which hydrogen and oxygen are produced. However, the sluggish kinetics of the OER and the high thermodynamic potential requirement of 1.23 V for the OWS limit the current performance of bias-free photoelectrochemical (PEC) systems to ∼3.5 mA/cm 2 . , Given that 90% of the overall energy requirements come from OER, alternative oxidative reactions could enable more efficient PEC systems.…”
mentioning
confidence: 99%
“…2,5,6 One such approach to realizing artificial photosynthesis is presented through the photochemical diode. 7,8 Photoanodes and photocathodes can be integrated through an ohmic contact, coupling both oxidative and reductive half-reactions in a single device. 9−11 Conventional approaches targeted the optimization of the overall water splitting (OWS) reaction in which hydrogen and oxygen are produced.…”
mentioning
confidence: 99%